2014
DOI: 10.2174/18715206113139990092
|View full text |Cite
|
Sign up to set email alerts
|

β2-Microglobulin-mediated Signaling as a Target for Cancer Therapy

Abstract: β2-microglobulin (β2-m) has become the focus of intense scrutiny since the discovery of its undesirable roles promoting osteomimicry and cancer progression. β2-m is a well-known housekeeping protein that forms complexes with the heavy chain of major histocompatibility complex class I molecules, which are heterodimeric cell surface proteins that present antigenic peptides to cytotoxic T cells. On recognition of foreign peptide antigens on cell surfaces, T cells actively bind and lyse antigen-presenting cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 85 publications
3
61
0
Order By: Relevance
“…Under normal physiological conditions, some amount of Β2M may be secreted into circulation from cell surfaces or as a result of intracellular release (24) and is removed from blood predominantly by the kidneys (5). Thus, the net concentration of serum Β2M is determined by its generation and secretion into serum, as well as its elimination by the kidneys, so that serum B2M concentration increases with elevated turnover of cells and/or reduced kidney function (6).…”
Section: Introductionmentioning
confidence: 99%
“…Under normal physiological conditions, some amount of Β2M may be secreted into circulation from cell surfaces or as a result of intracellular release (24) and is removed from blood predominantly by the kidneys (5). Thus, the net concentration of serum Β2M is determined by its generation and secretion into serum, as well as its elimination by the kidneys, so that serum B2M concentration increases with elevated turnover of cells and/or reduced kidney function (6).…”
Section: Introductionmentioning
confidence: 99%
“…Over-expression of β2M increases tumor growth and promotes migration and invasion of small lung cancer, prostate cancer, renal cancer, ovarian cancer, and breast cancer cells by the stimulation of epithelial-mesenchymal transition (EMT). In addition, β2M has multiple functions in tumor development and mediates tumorigenesis, metastasis and angiogenesis [13][14][15]. Previous studies demonstrated that β2M modulates its action in vitro via increased protein kinase A (PKA)/cyclic AMP-responsive element-binding protein (CREB) phosphorylation, VEGF expression, and cell survival, including the phosphatidylinositol 3-kinase (PI3K)/Akt and mitogen-activated protein kinase (MAPK) signaling pathways in human renal carcinoma cells [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…reported that HFE protein, a non-classical MHC class I member, interacts with β2-m to modulate iron homeostasis by interacting with the transferrin receptor (TFR) and its complex, TFRC, which together govern EMT and ROS in cancer cells. β2-m protected against the influx and accumulation of intracellular iron, and lower levels of intracellular iron activated HIF-1α and its target genes including EMT markers and VEGF [31,36]. Knocking down either the HFE protein or β2-m resulted in mesenchymal to epithelial transition (MET), a reversal of EMT, decreased cell proliferation and increased apoptosis in PCa cells [42].…”
Section: Osteomimicry In the Pca Bone Metastatic Phenotype Activatesmentioning
confidence: 99%
“…β2-m activates intracellular signaling axes mediated by ERK and sterol regulatory element-binding protein-1 (SREBP-1), that drive lipogenesis and lipid and lipid raft-mediated signaling and could potentially enhance the survival of cancer cells [34]. These results together with the demonstration that β2-m-mediated multiple downstream converging signaling pathways, including AR, lipid, iron and ROS [31,36,42,43], could exert powerful influences on the fate of PCa cells and their clinical behavior.…”
Section: Osteomimicry In the Pca Bone Metastatic Phenotype Activatesmentioning
confidence: 99%
See 1 more Smart Citation